Verbesserung der Betriebspunktauslegung durch Schneckensimulation - Schöppner, Volker; Austermeier, Laura; Trienens, Dorte (Wissenschaftlicher Arbeitskreis Kunststofftechnik)

The main factors influencing glass fiber shortening in the processing of bulk molding compounds (BMC) - Moritzer, Elmar; Scholle, Maximilian

Optimizing the Processing Performance of a Single Screw Extruder Using Live Simulations Based on Real Time Experimental Data - Köllermeier, Jonas; Schöppner, Volker

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

The Wave Must Be Right - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Plastic Insights)

Vorspannkraftrelaxation bei der Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)

Motivationsprofile zum Erwerb pädagogischen Wissens im Lehramtsstudium - Homt, Martina; Wehde, Janis; Bloh, Bea

Novel Straightening-Machine Design with Integrated Force Measurement for Straightening of High-Strength Flat Wire - Bathelt, Lukas; Scurk, Maximilian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Sensors)
In a punch-bending machine, wire products are manufactured for a wide range of industrial sectors, such as the electronics industry. The raw material for this process is flat wire made of high-strength steel. During the manufacturing process of the flat wire, residual stresses and plastic deformations are induced into the wire. These residual stresses and deformations fluctuate over the length of the semi-finished product and have a negative effect on the final product quality. Straightening machines are used to reduce this influence to a minimum. So far, the adjustment of a straightening machine has been performed manually, which is a lengthy and complex task even for an experienced worker. This inevitably leads to the use of inefficient straightening strategies and causes high rejection rates in the entire production process. Due to a lack of sensor information from the straightening operation, application of modern feedback control methods has not been practicable. This paper presents a novel design for a straightening machine with an integrated, precise straightening force measurement. By simultaneously monitoring the position of the straightening rollers, state variables of the straightening operation can be derived. Additionally, a tension control for feeding the flat wire is introduced. This is implemented to mitigate the disturbing effects caused by irregularities in the wire-feeding process. In the results of this article, the high precision of the developed force measurement design and its possible applications are shown.

Finite-Set Direct Torque Control via Edge Computing-Assisted Safe Reinforcement Learning for a Permanent Magnet Synchronous Motor - Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Deep Q Direct Torque Control with a Reduced Control Set Towards Six-Step Operation of Permanent Magnet Synchronous Motors - Haucke-Korber, Barnabas; Schenke, Maximilian; Wallscheid, Oliver (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Gym-Electric-Motor (GEM) Control: An Automated Open-Source Controller Design Suite for Drives - Book, Felix; Traue, Arne; Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Selbstverständlichkeit und Problematisierung. Husserls Programm der Phänomenologie - Philippi, Martina
Selbstverständlichkeiten in Verständlichkeiten überführen – dies ist das Credo der Phänomenologie Husserls. Ein zentrales Anliegen des phänomenologischen Programms ist es, die „vermeintlichen Selbstverständlichkeiten“ des Positivismus aufzudecken und zu klären; zugleich gibt Selbstverständlichkeit Anlass zu inhaltlichen Analysen, denn sie fungiert als Geltungsmodus des alltäglichen Lebensvollzugs, gespiegelt im Sinnbild von Boden und Horizont der Lebenswelt. Die Studie stellt Geltung, Einstellung und Perspektivwechsel als jene begrifflichen Werkzeuge heraus, mit denen Husserl dieses schwer greifbare Phänomen systematisch erschließt und methodisch wie inhaltlich in die Spannungsfelder von Theorie und Praxis, Doxa und Episteme, Lebenswelt und Wissenschaft einbettet. Darüber hinaus ergänzt sie mit dem psychopathologischen Ansatz Wolfgang Blankenburgs, was die Beschreibungsmacht der Phänomenologie an ihre Grenzen bringt: die Erfahrung der Selbstverständlichkeit im Lebensvollzug.
Keywords: Selbstverständlichkeit; Husserl; Phänomenologie

The Submission of Rebellious Cities in the Roman-German Empire - Kamp, Hermann (Peacemaking and the Restraint of Violence in High Medieval Europe)

Frame-Wise and Overlap-Robust Speaker Embeddings for Meeting Diarization - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

LibriWASN: A Data Set for Meeting Separation, Diarization, and Recognition with Asynchronous Recording Devices - Schmalenstroeer, Joerg; Gburrek, Tobias; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)

A Teacher-Student Approach for Extracting Informative Speaker Embeddings From Speech Mixtures - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

Achim Duchow: Blindes Vertrauen / Werkverzeichnis 1971–1993
Das Werkverzeichnis des Düsseldorfer Malers, Fotografen und Objektkünstlers Achim Duchow (1948 – 1993) lädt ein zur Wiederentdeckung eines komplexen OEuvres. Im spielerischen Umgang mit Autorschaft, Subjektivität und Medien, dem unmittelbaren Zugriff auf alle ihn bewegenden Themen ist ein Werk entstanden, das auch heute noch seine Wirkung entfaltet. In chronologischer Folge, unterbrochen von einzelnen Essays verzeichnet die Publikation als eine über 400-seitige Liste alle Phasen des Werks: Duchows Zusammenarbeit mit Sigmar Polke in den 1970er Jahren, seinen zweieinhalbjährigen Aufenthalt in Japan, seine Rückkehr 1981 in eine Kunstszene, die sich rasant in Richtung Marktgängigkeit verändert hatte, seine Arbeit an einem neuen Selbstverständnis als Künstler und Kulturarbeiter, seine malerische Auseinandersetzung mit deutscher Geschichte und Politik, mit Kolonialismus und Wiedervereinigung, aber auch mit dem Informel und dem Konstruktivismus. Das Werkverzeichnis katalogisiert alle auffindbaren Arbeiten sowie Texte von Duchow selbst. Weggefährt·innen und Historiker·innen geben einen Einblick in den radikalen Kontext seines Lebens.
Keywords: Malerei; Medienkunst; Fotografie; Düsseldorf; Hamburg; Japan; Bad Painting; Popart; Montage

Al Vostro Servizio - Schulze, Max (Buch Handlung Welt Bücher)
Buch Handlung Welt – in drei Worten − wurde von der Künstlerin Hilka Nordhausen 1976 im Hamburger Karolinenviertel eröffnet. Ein Laden, der Unmengen an Drucken, Heften, Broschüren, Taschenbüchern, Publikationen aus dem Underground, aus Übersee, der Kunst und Esoterik, auch selbstverlegte Bücher, Kataloge und Zines versammelte, die in wirren Stapeln halbhohe Tische bedeckten. Zwischen den überquellenden Bücherregalen fanden Lesungen und Performances statt, Filme und alles mögliche andere wurden projiziert. Fast jeden Monat entstand ein neues Wandbild in den Räumen. Die Buch Handlung Welt war bis 1983 in Hamburg der Ort für selbstorganisiertes künstlerisches Handeln − ein Anschlag auf die Wirklichkeit. Ein Konvolut dieser Bücher und Zeitschriften befindet sich im Nachlass von Hilka Nordhausen. 40 Jahre später stellt sich die Frage: Was bleibt von den Büchern, welchen Zeitgeist transportieren sie? Welche haben auch heute noch Bedeutung? Dieses Buch versammelt eine Reihe von subjektiven und widersprüchlichen Einschätzungen zu diesen Titeln, von jungen und mittelalten Künstler*innen und Wissenschaftler*innen.
Keywords: Buch Handlung Welt; Hilka Nordhausen; Achim Duchow; Martin Kippnberger

Dreckiges Informel: In Erwartung eines gebrochenen Arms - Schulze, Max (Achim Duchow: Blindes Vertrauen / Werkverzeichnis 1971–1993)
Keywords: Malerei; Düsseldorf; Bad Painting; Informell; Farbenlehre

Juryarbeit - Schulze, Max (Handbuch zur 90. Herbstausstellung des Kunstvereins Hannover)
Als größte Überblicksschau von regionalen Künstler:innen in Niedersachsen und Bremen gehört die Herbstausstellung des Kunstvereins Hannover seit ihrer ersten Ausgabe im Jahr 1907 zu den wichtigsten Ausstellungen im Land. Auch in ihrer 90. Ausgabe setzt die traditionelle Herbstausstellung den Fokus auf die lebendige hiesige Kunstszene.
Keywords: Kunst; Jury; Jahresausstellung; Manfred de la Motte; Marcel Duchamp

Religion in TV-Serien. Literaturbericht über praktisch-theologische Rezeptionsperspektiven der letzten Jahre - Pinsch, Jan Christian; Kirsner, Inge (Praktische Theologie)

Rezension von: Jörg van Norden: Verlust der Vergangenheit. Historische Erkenntnis und Materialität zwischen Wiedererkennen und Befremden, Frankfurt/M.: Wochenschau-Verlag 2022 - Hartung, Olaf (sehepunkte)

Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s)

Compensation of the Shrinkage Behavior Occurring in Cylindrical Components in the FDM Process - Koers, Thorsten; Magyar, Balázs (Macromolecular Symposia)
Fused deposition modeling (FDM) is an additive manufacturing process that can be used to manufacture three-dimensional thermoplastic components layer by layer. One disadvantage of FDM is the shrinkage of the components during the manufacturing process. The filament is molten in the nozzle, deposited layer by layer, and cools down again. During solidification, the filament shrinks inhomogeneously in the x/y/z direction, which leads to distortion of the component geometries. Particularly with higher nominal lengths and complex local geometries, there is a need for optimization with regard to dimensional accuracy. The aim of this paper is to counteract this on the software side with global as well as local shrinkage factors. The expected shrinkage within a layer is predicted with an in-house developed software. The geometric accuracy of the model is verified by experimental investigations on cylindrical test specimens. In these, the so-called clover effect occurs as a result of the shrinkage. The circular shape of the deposited layer is deformed by the distortion in the x–y plane comparable to a clover. Finally, the results are validated by analyzing a demonstrator in the form of a bracket.

Christine Moldrickx: Eendenbewustzijn
Keywords: Aquarell; Donald Duck; Entenhausen; Malbuch; Verlangen; Lust; Angst; Kunst

Data-driven identification of disturbances using a sliding mode observer - Götte, Ricarda-Samantha; Klusmann, Jo Noel; Timmermann, Julia (Proceedings - 33. Workshop Computational Intelligence: Berlin, 23.-24. November 2023)

"Always Contribute Back": A Qualitative Study on Security Challenges of the Open Source Supply Chain - Wermke, Dominik; Klemmer, Jan H.; Wöhler, Noah; Schmüser, Juliane; Sri Ramulu, Harshini; Acar, Yasemin; Fahl, Sascha (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

Pushed by Accident: A Mixed-Methods Study on Strategies of Handling Secret Information in Source Code Repositories - Krause, Alexander; Klemmer, Jan H.; Huaman, Nicolas; Wermke, Dominik; Acar, Yasemin; Fahl, Sascha (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

It’s like flossing your teeth: On the Importance and Challenges of Reproducible Builds for Software Supply Chain Security - Fourné, Marcel; Wermke, Dominik; Enck, William; Fahl, Sascha; Acar, Yasemin (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

"In Eighty Percent of the Cases, I Select the Password for Them": Security and Privacy Challenges, Advice, and Opportunities at Cybercafes in Kenya - Munyendo, Collins W.; Acar, Yasemin; Aviv, Adam J. (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

Ethical Frameworks and Computer Security Trolley Problems: Foundations for Conversations - Kohno, Tadayoshi; Acar, Yasemin; Loh, Wulf (CoRR)

A World Full of Privacy and Security (Mis)conceptions? Findings of a Representative Survey in 12 Countries - Herbert, Franziska; Becker, Steffen; Schaewitz, Leonie; Hielscher, Jonas; Kowalewski, Marvin; Sasse, M. Angela; Acar, Yasemin; Dürmuth, Markus (Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems, CHI 2023, Hamburg, Germany, April 23-28, 2023)

"We are a startup to the core": A qualitative interview study on the security and privacy development practices in Turkish software startups - Keküllüoglu, Dilara; Acar, Yasemin (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

"Oh yes! over-preparing for meetings is my jam :)": The Gendered Experiences of System Administrators - Kaur, Mannat; Sri Ramulu, Harshini; Acar, Yasemin; Fiebig, Tobias (Proc. ACM Hum. Comput. Interact.)

S3C2 Summit 2202-09: Industry Secure Suppy Chain Summit - Tran, Mindy; Acar, Yasemin; Cucker, Michel; Enck, William; Kapravelos, Alexandros; Kästner, Christian; Williams, Laurie A. (CoRR)

S3C2 Summit 2023-02: Industry Secure Supply Chain Summit - Dunlap, Trevor; Acar, Yasemin; Cucker, Michel; Enck, William; Kapravelos, Alexandros; Kästner, Christian; Williams, Laurie A. (CoRR)

S3C2 Summit 2023-06: Government Secure Supply Chain Summit - Enck, William; Acar, Yasemin; Cukier, Michel; Kapravelos, Alexandros; Kästner, Christian; Williams, Laurie A. (CoRR)

"Security is not my field, I’m a stats guy": A Qualitative Root Cause Analysis of Barriers to Adversarial Machine Learning Defenses in Industry - Mink, Jaron; Kaur, Harjot; Schmüser, Juliane; Fahl, Sascha; Acar, Yasemin (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

Lost and not Found: An Investigation of Recovery Methods for Multi-Factor Authentication - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (CoRR)

On Feature Importance and Interpretability of Speaker Representations - Rautenberg, Frederik; Kuhlmann, Michael; Wiechmann, Jana; Seebauer, Fritz; Wagner, Petra; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised speech disentanglement aims at separating fast varying from slowly varying components of a speech signal. In this contribution, we take a closer look at the embedding vector representing the slowly varying signal components, commonly named the speaker embedding vector. We ask, which properties of a speaker's voice are captured and investigate to which extent do individual embedding vector components sign responsible for them, using the concept of Shapley values. Our findings show that certain speaker-specific acoustic-phonetic properties can be fairly well predicted from the speaker embedding, while the investigated more abstract voice quality features cannot.

Explaining voice characteristics to novice voice practitioners-How successful is it? - Wiechmann, Jana; Rautenberg, Frederik; Wagner, Petra; Haeb-Umbach, Reinhold (20th International Congress of the Phonetic Sciences (ICPhS))

Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen.)

The Role of Response Time for Algorithm Aversion in Fast and Slow Thinking Tasks - Lebedeva, Anastasia; Kornowicz, Jaroslaw; Lammert, Olesja; Papenkordt, Jörg (Artificial Intelligence in HCI)

Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Putting Data Privacy Regulation into Action: The Differential Capabilities of Service Frontline Interfaces - Steinhoff, Lena; Martin, Kelly D. (Journal of Service Research)
Service frontline encounters between customers and service providers have been subject to fundamental changes in recent years. As two major change agents, technology infusion and data privacy regulations are inextricably linked and constitute a critical ethical and societal issue. Specifically, service frontlines—as represented by human or technological agents, or some hybrid form—rely on customer data for service provision, which subjects them to privacy regulations governing the collection, submission, access, and use of any customer data thus captured. However, scant research outlines the significant implications of evolving data privacy regulations for service frontline encounters. To advance knowledge in this domain, this research distills six key dimensions of global data privacy regulations (fairness, data limits, transparency, control, consent, and recourse). Employing an intelligences theoretical lens, the authors theorize how these dimensions might become differentially manifest across three service frontline interface types (human-based, technology-based, and hybrid). Carefully intersecting the need for varying intelligences across data privacy regulatory dimensions with the abilities of service frontline interfaces to harness each intelligence type, this study offers a novel conceptual framework that advances research and practice. Theoretical, managerial, and policy implications unfold from the proposed framework, which also can inform a future research agenda.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Belastungsgerechte Auslegung automobiler Leichtbaustrukturen aus pressgehärtetem Stahl und kohlenstofffaserverstärktem Kunststoff - Triebus, Marcel
Hybride Bauteile, welche aus Werkstoffen mit hohen spezifischen Festigkeiten bestehen, können zu einem signifikanten Leichtbau im Automobil beitragen. Diese Arbeit erforscht die hybride Kombination von pressgehärtetem Stahl und kohlenstofffaserverstärktem Kunststoff. Ausgehend von einer Analyse bestehender Karosseriestrukturen erfolgt ein Konzept für eine hybride B-Säule. Das Potential zur Gewichtsreduzierung durch das hybride Bauteilkonzept wurde dabei zu 57 % identifiziert, welches jedoch nur bei Sicherstellung einer intakten Grenzfläche erreicht wird. Zur Erlangung der Grenzflächenfestigkeit bei charakteristischen Belastungsprofilen wurde ein Verfahren zur Einbringung makroskopischer Formschlusselemente im Presshärteprozess entwickelt. Durch diese Formschlusselemente wird eine Steigerung der Scherfestigkeit der hybriden Komponenten von über 300 % erreicht. Die gewonnenen Erkenntnisse werden abschließend zur Auslegung einer hybriden B-Säule angewendet.

Primary school teachers’ perspectives on the quality of inclusive education - Görel, Gamze; Franzen, Katja; Hellmich, Frank (Teachers and Teaching)
Keywords: Arts and Humanities (miscellaneous); Education

Zwischen lebensunwertem und selbstbestimmtem Leben. Impulse des 20. Jahrhunderts für eine ableismuskritische Religionspädagogik - Neumann, Anna (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Jesus heilt. Warum nicht alle? Heilungswunder aus der Perspektive von Menschen mit Behinderung - Neumann, Anna; Kammeyer, Katharina (Religion 5-10)